1851-1852 Ga. Laws 269 - (:unkn) unknown (My University, 1852)
No. 165: Prohibited the concealed carry of any pistol, dirk, sword in a cane, spear, Bowie knife, or any other kind of knives manufactured and sold for the purpose of offense or defense.
Keywords: CARRY - CONCEALED